Visualisasi Informasi Nilai Pada Sistem Informasi Akademik MA Hidayatus Syubban Semarang (Information Technology and Telematics, 2015)
ABSTRACT MA Hidayatus Syubban Semarang is a high quality Islamic school.The acilities and infrastructure has been supported by computer technology,  but is still not optimally used and data processing is still using manual systems, therefore the presentation of information often is not effective and efficient. In data processing which alwayss increasing in number, requiring tools ( computer ) that can access the data quickly. Therefore constructing an information technology that can help to overcome these problems in order to make the presentation of information from students information and student’s data, teacher’s data, the lessons and classes learning could be running optimally and efficiently. The purpose is to analyze the data and the existing systems as well as fixing it sowe can  present the academic information accurately and appropriately. This system provides information in the form of tables and graphs. Hightchart Framework  is used to display the chart. Keywords: visualization of information , academic information systems